“Just a Little Respect”: Effects of a Layoff Agent’s Actions on Employees’ Reactions to a Dismissal Notification Meeting - Richter, Manuela (Journal of business ethics, 2018)
A layoff is a threatening yet common event which employees might face at some point in their working lives. In two scenario-based experiments (total N = 344), we investigated which actions of a layoff agent (i.e., who delivers the layoff notice) during a dismissal notification meeting may contribute to laid-off employees’ fairness judgments and negative attitudes toward the employer. In general, the extent to which layoff victims were treated with respect was consistently found to increase perceptions of interpersonal and procedural fairness and to mitigate negative attitudes toward the employer. Further results showed that layoff victims preferred to be given an adequate (vs. inadequate) explanation of the reasons for the layoff and to receive notice from the direct supervisor (vs. an external consultant). Relationships between the layoff agent’s actions and layoff victims’ negative attitudes toward the employer were mediated by perceptions of procedural fairness. In addition, delegating the layoff agent’s task to an external consultant increased perceived psychological contract breach. Our findings have important implications for organizational justice research and for the managerial practice of implementing fair layoffs. In particular, small actions, such as treating employees with respect, might be of benefit both to humans and organizations.